A Human Capital Perspective on Behavioral Factors Affecting Customers’ Acceptance of Crowd Logistics: A Systematic Literature Review - Arvid Muzanenhamo; Marcia Mkansi (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
This paper provides a systematic review of the customer’s behavioral deliberations that govern their choice to participate in a crowd-logistics market. Little attention has been given to the crowd logistics platforms and small businesses. This paper presents the analysis of customers' crowd logistics adoption from a behavioral perspective. The study applied a systematic literature review method and examined previous literature on crowd logistics from Science Direct and Taylor and Francis. Systematic literature review involve the principles of transparency, rigor, and replicability, which bring significant benefits over traditional literature reviews through greater objectivity. The findings suggest that customers’ ability to use technology, safety considerations, desire to make social connections, trust, and convenience are the factors that influence people’s decisions to participate in the crowd-logistics market. The findings of this study are valuable for empirical research in a particular setting and strengthen the body of knowledge on the adoption or acceptance of the crowd-logistics concept.